The Long, Long Letter - Spurr, Elizabeth; Catrow, David (New York : Hyperion, 1996)
Mother's long, long letter brings Aunt Hetta surprise and adventure, as the loose pages bury her house and keep her warm during the winter.
P-3.
Accelerated Reader AR
Keywords: Letters -- Fiction; Aunts -- Fiction; Tall tales